The lamentation over the destruction of Ur - Samet, Nili (Mesopotamian civilizations ;, 2014)
The goal of this book is to present a revised edition of the Sumerian Lamentation over the Destruction of Ur, a lament bewailing the fall of the glorious Ur III kingdom in 2004 B.C.E.Lamentation is a well-known genre in world literature. Laments of various types are part of the cultural legacy and literary corpus of many societies, from ancient to modern times, and Sumerian literature is no exception. However, Mesopotamian lamentation literature includes a significant body of laments belonging to a unique and almost unparalleled genre--the genre of lamentations over the destruction of cities and temples. This genre has no known ancient parallel outside the ancient Near East; more specifically, it is almost exclusively attested in Sumerian and biblical literature. The Lamentation over the Destruction of Ur is the most famous and important exemplar of the city-laments.In this updated and revised publication of the Lamentation over the Destruction of Ur, Samet provides an introductory discussion of Sumerian city-laments in general; a full presentation of the text of the Ur Lament, including transliteration, translation, and an extensive philological commentary; and an accounting of the extant textual witness in score format. Plates with color photos of many texts are included.